2007
DOI: 10.1901/jeab.2007.22-07
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Avoidance Response Functions in Accordance With Same and Opposite Relational Frames

Abstract: Research on the emergence of human avoidance behavior in the absence of direct contact with an aversive event is somewhat limited. Consistent with work on derived relational responding, the present study sought to investigate the transformation of avoidance response functions in accordance with the relational frames of Same and Opposite. Participants were first exposed to nonarbitrary and arbitrary relational training and testing in order to establish Same and Opposite relations among arbitrary stimuli. The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
85
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 27 publications
12
85
0
4
Order By: Relevance
“…To illustrate, if choosing Stimulus X in the presence of Stimulus A is taught (i.e., A-X), and choosing Stimulus Y in the presence of Stimulus A (i.e., A-Y) is also taught, it is likely that untrained relations will emerge between X and A, Y and A ("symmetry"), X and Y, and Y and X ("equivalence"), in the absence of any feedback. When this occurs, a stimulus equivalence relation is said to have formed among the relata (Dymond & Roche, 2013;Hayes & Hayes, 1992). The emergence of untrained verbal relations such as these may, it is claimed, help explain the patterns of indirect, nonperceptually based fear generalization often seen in anxiety disorders and which arise in the apparent absence of a conditioning history with the feared object or event (Dymond & Roche, 2009;.…”
Section: Nonperceptual Fear Generalization: the Role Of Symbolic Genementioning
confidence: 99%
See 2 more Smart Citations
“…To illustrate, if choosing Stimulus X in the presence of Stimulus A is taught (i.e., A-X), and choosing Stimulus Y in the presence of Stimulus A (i.e., A-Y) is also taught, it is likely that untrained relations will emerge between X and A, Y and A ("symmetry"), X and Y, and Y and X ("equivalence"), in the absence of any feedback. When this occurs, a stimulus equivalence relation is said to have formed among the relata (Dymond & Roche, 2013;Hayes & Hayes, 1992). The emergence of untrained verbal relations such as these may, it is claimed, help explain the patterns of indirect, nonperceptually based fear generalization often seen in anxiety disorders and which arise in the apparent absence of a conditioning history with the feared object or event (Dymond & Roche, 2009;.…”
Section: Nonperceptual Fear Generalization: the Role Of Symbolic Genementioning
confidence: 99%
“…Fear and avoidance responses conditioned to one of these stimuli may then alter or transform the functions of other, untrained relations in terms of "same" and "opposite." Dymond et al (2007Dymond et al ( , 2008) exposed participants to a signaled avoidance task, during which responding in the presence of the stimulus B1 cancelled a scheduled US presentation. Another stimulus, B2, was never followed by the US.…”
Section: Symbolic Avoidance Generalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, many behavior analysts now agree that verbal processes are likely involved in the acquisition of complex forms of anxiety (e.g., Augustson & Dougher, 1997;Dougher, 1998;Dymond & Rehfeldt, 2000;Dymond & Roche, 2009;Forsyth, 2000;Forsyth & Eifert, 1996;Friman, et al, 1998;Hayes, Strosahl, & Wilson, 1999;Hayes & Wilson, 1993Tierney & Bracken, 1998). The role of verbal behavior in behavior-analytic accounts of anxiety has been revisited with a view to addressing gaps in our understanding of the processes involved in the development, maintenance, and treatment of clinical anxiety (e.g., Dougher, Hamilton, Fink, & Harrington, 2007;Dymond, Roche, Forsyth, Whelan, & Rhoden, 2007;Wray, et al, 2009).…”
mentioning
confidence: 99%
“…The avoidance response was shown to transfer to the other members of the particular equivalence class and not to members of the other equivalence class (A2-B2-C2-D2). The authors used the observed transfer of function across stimulus equivalence classes to help explain, at least in part, the aetiologies of avoidance responses that appear to have emerged in the absence of any explicit history of reinforcement for avoidance in the natural environment, while acknowledging that as a mere experimental analogue the levels of conditioned responding observed were not clinically significant (see also Dougher, et al, 2007;Dymond, et al, 2007;Friman, et al, 1998;Roche, Barnes-Holmes, Smeets, Barnes-Holmes, & McGready, 2000).…”
mentioning
confidence: 99%